Ovelhas negras: uma abordagem genética de três contos de Caio Fernando Abreu - Ramalho, Sabrina Rieckel (2015)
This paper aims the genetic analysis of the following manuscripts: Introdução ao Passo da Guanxuma, Noites de Santa Teresa and Anotações Sobre um Amor Urbano which are part of the book Ovelhas Negras by Caio Fernando Abreu. Our proposal is to follow the short stories genesis, through their manuscrips, typescripts and printed papers that make part of our prototext, to describe and analyze the several versions of it and to reflect on the text instability along the writer s fictional process. In order to reach our analysis, we take hand of theoretical studies from the Genetic Criticism, by authors such as Pierre-Marc de Biasi, Almuth Grésillon, Cecília Salles, Philippe Willemart who enlighten our understanding about the movements of the writing process.